Penyelenggaraan Pariwisata Olahraga: Perspektif Rekomendasi Pemerintah Daerah - Putra Thama, Aditya; Dharmawan, Ni Ketut Supasti (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 2 (2019)DO - 10.24843/AC.2019.v04.i02.p05, 2019)
Current sports activities are quite closely related to tourism. Tourism is the main source of livelihood for the people of Bali. Along with the development of sports in Bali, the implementation of sports tourism was also developed as an option in the development of local tourism. Bali Provincial Sports Regulation regulates sports tourism in Bali. However, the provisions of Article 14 paragraph (2) of the regulation require regional government recommendations prior to the implementation of sports tourism, which if not fulfilled can be subject to criminal sanctions in contravention of the SKN Law and the implementing regulations give rise to norm conflicts. The purpose of this study is to study the implementation of sports tourism based on the Bali Province Sports Regulations and analyze criminal sanctions for not being given the recommendations of the regional government by the organizers. The method used in this study is a normative legal research method with a statutory approach. The results of the study show that based on the Bali Provincial Sports Regulations the implementation of sports tourism must obtain recommendations from the regional government as Article 14 paragraph (2) of the Provincial Regulation on Sport in Bali. However, higher legal provisions related to sports, namely the SKN Law does not regulate this. The SKN Law which is a reference for organizing sports only requires a recommendation from the relevant organization of sports branch as Article 51 paragraph (2). The criminal provisions as Article 65 paragraph (1) of the Bali Province Sports Regulations for organizers who do not have a recommendation from the regional government are irrelevant and seem excessive considering the recommendation is an administrative requirement for an activity, it will be more relevant if administrative sanctions are imposed rather than criminal sanctions. In the event that this occurs, it will refer to the provisions of the SKN Law as well as the implementation rules. Kegiatan olahraga saat ini cukup erat kaitannya dengan pariwisata. Pariwisata merupakan sumber mata pencaharian utama bagi masyarakat Bali. Seiring dengan berkembangnya olahraga di Bali, penyelenggaraan pariwisata olahraga juga dikembangkan sebagai salah satu pilihan dalam pengembangan pariwisata lokal. Perda Keolahragaan Provinsi Bali mengatur pariwisata olahraga di Bali. Namun ketentuan Pasal 14 ayat (2) pada perda tersebut yang mewajibkan rekomendasi pemerintah daerah sebelum penyelenggaraan pariwisata olahraga, yang apabila tidak dipenuhi dapat dikenakan sanksi pidana bertentangan dengan UU SKN maupun peraturan pelaksanaannya memunculkan konflik norma. Tujuan studi ini yakni untuk mengkaji penyelenggaraan pariwisata olahraga berdasarkan Perda Keolahragaan Provinsi Bali dan menganalisis sanksi pidana atas tidak dikantonginya rekomendasi pemerintah daerah oleh penyelenggara. Metode yang digunakan dalam penelitian ini adalah metode penelitian hukum normatif dengan pendekatan perundang-undangan. Hasil studi menunjukkan bahwa berdasarkan Perda Keolahragaan Provinsi Bali penyelenggaraan pariwisata olahraga wajib mendapatkan rekomendasi dari pemerintah daerah sebagaimana Pasal 14 ayat (2) Perda Keolahragaan Provinsi Bali. Namun ketentuan perundang-undangan yang lebih tinggi terkait dengan keolahragaan, yakni UU SKN tidak mengatur demikian. UU SKN yang merupakan acuan dari penyelenggaraan keolahragaan hanya mewajibkan adanya rekomendasi dari induk cabang olahraga yang bersangkutan sebagaimana Pasal 51 ayat (2). Adapun ketentuan pidana sebagaimana Pasal 65 ayat (1) Perda Keolahragaan Provinsi Bali bagi penyelenggara yang tidak mengantongi rekomendasi dari pemerintah daerah tidaklah relevan dan terkesan berlebihan mengingat rekomendasi adalah sebuah syarat administrasi dari sebuah penyelenggaraan kegiatan, maka akan lebih relevan jika dikenakan sanksi administratif daripada sanksi pidana. Dalam hal itu terjadi, maka akan mengacu pada ketentuan UU SKN maupun aturan pelaksanaannya.